A Hollow Extrusion Die for Big Square Tube Profiles of Al-alloy. (March 2018) - Huang, Xuemei; Deng, Rurong
Abstract: The factors on premature failure of the traditional extrusion die for the big square tube profiles were introduced. And the characteristics of the conventional structure were analyzed. A new type of hollow die structure for these profiles was presented. And the composition elements of the new die structure were described, including its advantages. According to the comparison conventional with new die structure in use, it was shown that the new die structure has obvious advantages, it could greatly improve the die life. This is a type of die structure which is worth promoting.